Empirical relationships between hardness, replica and strain and their roles in health monitoring based life assessment for aged power plant materials. (October 2022) - Bonetti, R.; Morris, A.; Shipway, P.H.; Sun, W.
Abstract: In this paper, for the first time, a holistic empirical lifing approach, which accommodates the on-site information of replica, hardness and strain, is established based on a large amount of outage inspection data on ageing high temperature parent ½Cr½Mo¼V (CrMoV) material and has been used to illustrate how such routinely collected inspection data can be better utilized to provide the plant operator with predictions of residual creep life. The model differentiates between long term and persistent thermal softening behaviour revealed by change in hardness over time and short-term creep cavitation that accelerates material damage. Importantly the models developed are designed to be used iteratively with surface replica and hardness data available from an outage inspection. The study shows that the availability of more data will enable further refinements, but more importantly it emphasises the importance of systematically capturing this data and processing at the time of inspection to forecast residual life and then updating and tuning the model periodically at future inspections. The capture of strain data from pipe diametral measurements is also a routine outage activity and this data is included in the case study to demonstrate the capabilities in the residual life forecast by the new methods. Highlights: Novel empirical relationships defined using replica, hardness, strain for ageing CrMoV steels. Use of long-term historic field inspection data. Residual lifing capability for high temperature ageing materials. Demonstration on life forecast via a case study.